Angio-associated migratory cell protein (AAMP) interacts with cell division cycle 42 (CDC42) and enhances migration and invasion in human non-small cell lung cancer cells. (1st April 2021) - Yao, Shun; Shi, Feifei; Mu, Ning; Li, Xiaopeng; Ma, Guilin; Wang, Yingying; Sun, Xiaoyang; Liu, Xiangguo; Su, Ling
Abstract: Angio-associated migratory cell protein (AAMP) is considered a pro-tumor protein, which contributes to angiogenesis, proliferation, adhesion, and other biological activities. Although AAMP is known to facilitate the motility of breast cancer cells and smooth muscle cells by regulating ras homolog family member A (RHOA) activity, the function of AAMP in the metastasis of non-small cell lung cancer (NSCLC) cells still remains unknown. In the present study, AAMP was upregulated in non-small cell lung carcinoma, and was found to promote migration and invasion in NSCLC cells. Further experiments demonstrated that AAMP interacted with cell division cycle 42 (CDC42) and promoted its activation, resulting in the formation of cellular protrusions. Subsequently, we found that AAMP enhanced CDC42 activation by impairing the combination of rho GTPase activating protein 1 (ARHGAP1) and CDC42. Taken together, we revealed and elucidated the critical role of AAMP in the migration and invasion of NSCLC cells and presented a new potential target for lung cancer therapy. Highlights: Angio-associated migratory cell protein (AAMP) enables breast cancer cell motility. The role of AAMP in non-small cell lung cancer (NSCLC) cells is unclear. AAMP is upregulated in NSCLC cells, and promotes their migration and invasion. AAMP activates CDC42, inhibits ARHGAP1 binding, and increases cellular protrusions. Overall, AAMP may be a new potential target for lung cancer therapy.